1997
DOI: 10.1016/s0735-1097(97)00167-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of Exercise Echocardiography in Women With Known or Suspected Coronary Artery Disease

Abstract: In this large cohort of women, exercise echocardiography provided key prognostic information incremental to clinical and exercise testing data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(30 citation statements)
references
References 30 publications
3
26
0
1
Order By: Relevance
“…Of the latter, 851 patients were involved in 2 previous studies that used separate end points. 9,10 The clinical, exercise, and echocardiographic data of these patients were prospectively entered into separate databases, and follow-up was obtained from 1998 to 1999, after which the data were merged. Consent was obtained before testing, and the study was approved by the Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the latter, 851 patients were involved in 2 previous studies that used separate end points. 9,10 The clinical, exercise, and echocardiographic data of these patients were prospectively entered into separate databases, and follow-up was obtained from 1998 to 1999, after which the data were merged. Consent was obtained before testing, and the study was approved by the Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…23 Previous studies with exercise echocardiography have indicated that the imaging component of this test adds incremental and independent information to the results of standard exercise testing. [7][8][9][10][11][12] A normal exercise echocardiogram is associated with a risk of Ͻ1% per year over the first 6 years of follow-up, with a subsequent small increase that most likely reflects progressive coronary artery disease.…”
Section: Assessment Of Risk In Patients With Stable Chronic Coronary mentioning
confidence: 99%
See 1 more Smart Citation
“…Women with no ECG or echocardiographic evidence of ischemia had an excellent (96%) cardiac event-free survival over Ͼ3 years of follow-up, in contrast to a much higher cardiac event rate in those women with ECG and echocardiographic findings consistent with ischemia (cardiac eventfree survival of 55%). 103 In the same study, women with positive ECG findings and negative echocardiographic findings with stress had a longer event-free survival than women with negative ECG findings but echocardiographic findings consistent with ischemia. 103 The prognostic value of exercise echocardiography appears to be similar in men and women.…”
Section: Prognostic Valuementioning
confidence: 85%
“…103 In the same study, women with positive ECG findings and negative echocardiographic findings with stress had a longer event-free survival than women with negative ECG findings but echocardiographic findings consistent with ischemia. 103 The prognostic value of exercise echocardiography appears to be similar in men and women. 55,104 Similarly, exercise SPECT provides more prognostic value than ST-segment depression alone in women.…”
Section: Prognostic Valuementioning
confidence: 85%